Analysis of laboratory test ordering patterns in relation to costs at Brits District Hospital. - Mhlanga, Themba Wilfred (My University, 2014)
Laboratory tests are considered a critical clinical intervention in the diagnosis and treatment of various medical conditions. However, ordering of laboratory tests is not immune from abuse (under / over-use), which necessitates that the service be effectively managed. It has been a matter for concern that there actually are no benchmarks in existence against which district hospitals laboratory test ordering patterns can be measured. This study concerns the generation and compilation of a body of knowledge that will serve as a baseline / benchmark for comparison purposes on a month-to-month basis at Brits District Hospital, as well as for comparisons with other district hospitals, towards the development of best practices.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Public Health in the field of Hospital Management May 2013
Keywords: Costs and Cost Analysis; Diagnosis, Laboratory